(untitled) (مجلة إحالات, 2025)
ملخص: المتن الأدبي – كما النقدي - عند عمار بلحسن قيمة إبداعية لها سجالاتها الموضوعاتية المؤطرة لها ، حيث تصنع تجربة الكتابة حيزها من حيثيات للحضور ولاستجلاء الذات عبر تموّجات الخطاب ، لتتمثّل أسئلةً تتقلص أحيانا لاحتضان هويةٍ خصوصيةٍ تقبع في خرائط "الذات " / الأنا الفردية وتتمدّد أحايينَ أخراة لملامسة فضاءات المعايَنَة الفاحصة للخطوط الموازية لتلك الهوية ؛ خطوط تصنع هوامش للاختلاف والمغايَرة . وباعتبار الكتابة أيقونة جامعة لطروحات " الخاص " و " الجمعي " فقد ظلّ دوما يخوض في ثنائيات العودة نحو الذات / الأنا والسياحة في عوالم الوجود ليرسم واقعا تتمطّى خرائطه وحدوده التعبيرية حسب سياقاته النصية. ومن خلال هذه الورقة البحثية سنحاول بسط التفاصيل المعايِنَة لقيم النص التعبيرية بين مطارحات الهوية باعتبارها مجالا للرؤية الخصوصية المتجلية في استحضار " الأنا " وأسئلة الاختلاف النابعة أساسا من الوعي بهذه " الأنا " وبهوامشها التي تؤطر خلفيات " السؤال " المعبِّر عن فيوضات استشعار الواقع والمأمول ؛ أو الكائن والممكن . الكلمات المفتاحية: - الكتابة – الهوية – الاختلاف – الواقع – المأمول . Abstract : The literary text of Ammar Belhassan is a creative value for its thematic debates. The experience of writing makes its place in terms of presence and self-discovery through the discourse. The questions are sometimes reduced to embracing a specific identity that lies in individual self-maps. To touch the viewing spaces of the parallel lines of that identity; lines that create margins for difference and variance. As a university icon of the "private" and "collective" expositions, he has always been engaged in the dualism of self-return / ego and tourism in the realms of existence to paint a reality whose maps and expressive boundaries are dictated by its textual contexts. Through this paper, we will attempt to delineate the preview of the values of expressive text between identity chases as a field of private vision manifested in the evocation of the ego and questions of difference stemming primarily from the awareness of this ego and its margins that frame the "question" Object and possible. key words: - Writing - Identity - Difference - Reality - Hope.